Kualitas Pelayanan Administrasi Kependudukan Pada Kelurahan Tanjung Perak (studi Penggabungan Kelurahan Perak Utara dan Perak Timur Kecamatan Pabean Cantian Kota Surabaya) - Febrianti, Valentina; Eprilianto, Deby Febriyan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Public service is one of important things to fulfill the needs of the community. However, there are still many public servicess that do not satisfy the community. So that many updates and strategies issued by the government to realize quality services. Providing public services in merging two urban villages into one is certainly not an easy thing and there are certainly many challenges. Therefore, in this study, researchers are interested in examiningg public services in tanjung Perak Village as a village office that is currently experiencing a merger of villages, which initially merged North Perak and east Perak Villages into one. The purpose of this study was to describe the quality of population administration services in Tanjung Perak Villages, Pabean Cantian district, Surabaya City). The type of research uses the quality theory by Hadiyati, et al (2017) which consists of 7 aspect, namely infrastructure, employess, administrative services, trust, information transparency, access dan equality. The result of this study indicate that the services provided can be said to be quite good and the aspects that support are aspects of access and equality. While the aspects that need to be improved are the infrastructure aspect of the lack of waiting rooms and ineffective queues so that it is necessary to reuse the queue counter machine to be effective and efficient, the employess aspect is that there are still employees who communicate with colleagues when servig the community, the aspect of clarity of waiting time and the aspect of trust from the lack of community support, seen that there are still many people who do not change their identity because they feel they do not need if their daily activities.